2012
DOI: 10.1002/pssa.201200056
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical oxidation of ionic liquids at highly boron doped diamond electrodes

Abstract: An electrochemical oxidation using a highly boron‐doped diamond (BDD) electrode has been tested for the treatment of solutions containing ionic liquids (ILs). The double‐sided Si/highly BDD electrodes were synthesized by microwave plasma enhanced chemical vapour deposition (MW PE CVD). Investigation of the electrode surface with scanning electron microscopy (SEM) confirmed that the synthesized layers were continuous and formed densely packed grain structure. The structure of BDD was confirmed by Raman spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Therefore, it is necessary that additional research be undertaken to find other economical, stable, and efficient materials that can be used in electrolysis as electrodes or the BDD electrode may be modified to generate an electrochemical BDD system that integrates the three abovementioned important characteristics . The results of the electrochemical oxidation of ILs in the presence of the BDD electrode demonstrate that the anionic group influences the electrochemical process; for example, the chloride anion enhances the degradation of the cation of ILs. The anionic 4‐toluenesulfonate group, in contrast, competes with the imidazolium cation for the anodically produced HO .…”
Section: Degradation Of Ionic Liquidsmentioning
confidence: 99%
“…Therefore, it is necessary that additional research be undertaken to find other economical, stable, and efficient materials that can be used in electrolysis as electrodes or the BDD electrode may be modified to generate an electrochemical BDD system that integrates the three abovementioned important characteristics . The results of the electrochemical oxidation of ILs in the presence of the BDD electrode demonstrate that the anionic group influences the electrochemical process; for example, the chloride anion enhances the degradation of the cation of ILs. The anionic 4‐toluenesulfonate group, in contrast, competes with the imidazolium cation for the anodically produced HO .…”
Section: Degradation Of Ionic Liquidsmentioning
confidence: 99%
“…Rough surface introduces the loss of coherence of the reflected light wave and increases the diffuse part of the reflectance [19]. This effect manifests itself as a drop in oscillation amplitude and the mean value in the interference signal, as presented in Fig.…”
Section: Influence Of Film Surface Roughnessmentioning
confidence: 95%
“…The trends in roughness and refractive index were taken from our previous studies based on Raman spectroscopy and AFM/SEM measurements [19,20]. Deconvolution of Raman spectra gives the sp 3 …”
Section: Theoretical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several papers demonstrated that other biorefractory compounds such as pesticides, pharmaceuticals and dyes can be completely mineralized with the high current efficiency [16][17][18][19].…”
mentioning
confidence: 99%